2020
DOI: 10.1007/s10530-019-02178-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-native mollusks throughout South America: emergent patterns in an understudied continent

Abstract: Non-native species have been introduced at escalating rates during the last decades, mainly due to the dispersion generated by the increasing trade and transport worldwide. Mollusks, the second largest metazoan phylum in terms of species richness, are no exception to this pattern, but, to date, a comprehensive synthesis of non-native mollusk species (NNMS) in South America was not available. For this purpose, an e-discussion group was formed with malacologists and taxonomists from South America, where we excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 65 publications
1
46
0
14
Order By: Relevance
“…Land gastropods (native + non-native) in Argentina comprise 270 species belonging to 80 genera, 38 families, and 20 superfamilies (Table 1S). From this total number, 28 species in 17 families are non-native, mainly from European or southeastern Asian origin (Darrigran et al, 2020; Rumi et al, 2010). Odontostomidae, Bulimulidae (Orthalicoidea), Epiphragmophoridae (Helicoidea), and Charopidae (Punctoidea) are the most speciose families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Land gastropods (native + non-native) in Argentina comprise 270 species belonging to 80 genera, 38 families, and 20 superfamilies (Table 1S). From this total number, 28 species in 17 families are non-native, mainly from European or southeastern Asian origin (Darrigran et al, 2020; Rumi et al, 2010). Odontostomidae, Bulimulidae (Orthalicoidea), Epiphragmophoridae (Helicoidea), and Charopidae (Punctoidea) are the most speciose families.…”
Section: Resultsmentioning
confidence: 99%
“…Some regional species lists support major species richness in Brazil, Peru (Ramírez et al, 2003; Salgado and Coelho, 2003), and a major phylogenetic diversity in Colombia and Ecuador, although more in-depth and more complete biodiversity studies on native species should be carried out. Remarkably, an opposite situation occurs with the study of invasive species in South America, where detailed researches have been carried out as a consequence of the economic interest they attract (Darrigran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of non-native species (potential invasive species) is a main cause of biodiversity loss (Gallardo et al 2018). Darrigran et al (2020) identified four hotspot areas for non-native species of molluscs (both aquatic and terrestrial) in South America, which require special attention for biodiversity conservation, not only because they are potential entry points for non-native species, but also because they coincide with hotspots of high endemism (Darrigran et al 2020). Identifying entry points of non-native molluscs, such as through large cities, ports, or airports (Darrigran et al 2020), are a vital step to identify hotspots for conservation action.…”
Section: Patterns Of Threatmentioning
confidence: 99%
“…El asentamiento de L. fortunei en los ecosistemas ha presentado un alto impacto tanto en el ambiente natural (Darrigran y Damborenea, 2011) como en las infraestructuras humanas (Darrigran, et al, 2020). Se han documentado cambios en la comunidad bentónica (Linares, et al, 2017;Silva, et al, 2020), fitoplanctónica (Boltovskoy, et al, 2015a(Boltovskoy, et al, , 2013 y zooplanctónica (Rojas Molina, et al, 2015), así como su capacidad de incorporarse a las tramas tróficas de los peces (Garcia y Protogino, 2005;González-Bergonzoni, et al, 2020;Penchaszadeh, et al, 2000).…”
Section: Introductionunclassified